Analysis Of Food Security In Rice Farming Households That Experience Land Fragmentation In Buay Madang Sub-District, OKU Timur District - Munajat, Munajat; Permatasari, Fifian; Pusvita, Ema (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Fragmentation is agricultural land that is scattered or not in one whole area of land. Penelitian diakukan di Kecamatan Buay Madang Timur, Kabupaten Ogan Komering Ulu (OKU) Timur. Metode penelitian yang digunakan penelitian ini adalah metode studi kasus. Metode pengambilan sampel dilakukan secara acak serta berasal dari anggota populasi yang ada. Responden di ambil dari tiga desa yaitu Desa Tebat Jaya, Aman Jaya, Desa Sukaraja dan Desa Sridadi, dengan alasan keempat desa ini merupakan desa yang paling banyak terjadi fragmentasi lahan, dengan kriteria luas lahan lebih dari 1 Ha. Based on the results of the study using formula calculations, the level of food security for rice farming households experiencing land fragmentation in Buay Madang Timur District was 49.78% of total household expenditure. That is, according to the criteria, if the share of household food expenditure is 60%, household is said to be food insecure. Thus the tolerance value for the percentage share of household food expenditure is 60% assuming the ideal value of the share of household food expenditure is 49.78% of total household expenditure, meaning food security. Factors that affect the food security of rice farmers who experience land fragmentation in Buay Madang Timur District, OKU Timur Regency are land area (x1), access to food (x2), income (x3), price (x4) have a significant effect while length of education (x5 ) has no real effect.